NEW ACCESSIONS OF BRASSICA OLERACEA L. IN VIR PLANT COLLECTION - A. M. Artemieva (Овощи России, 2017)
Varieties of Brassica oleracea L. are widespread and favorite crops, where among them the head cabbage and cauliflower are the most economically important. Russia takes third place after India and Chine among countries with largest production areas and gross yield for the crop. In Russia, the area sown to cabbage is about 27 thousand hectares. 728 cultivars and hybrids of eight cabbage crops including 528 hybrids have been added in State Register of Breeding Achievements of Russian Federation in 2017. The collection of Brassica oleracea L. totally contains of 2421 accessions and takes first place at number of collected items among the world’s plant genbanks. The phenotyping, genotyping, passportization, development of core collection and trait collection as well as initial breeding accessions, covering all genetic diversity have been carried out at department of genetic resources of vegetables and melons at VIR. Selection of most promising accessions is performed to find genes and sources for economically valuable traits to develop proper lines and hybrids. There are the enrichment of the collection by means of ordering and gathering in expeditions, the improvement of methods of phenotyping and development of database for all biological accessions studied at the department. In 2007-2016, 255 accessions of Brassica oleracea L. have been included into collection to be used in different national breeding programs.